Anti-Angiogenic Drugs Inhibit Interstitial Lung Disease Progression in Patients With Advanced Non-Small Cell Lung Cancer - Wang, Yanning; Gong, Xiaoling; Hu, Yuxuan; Yi, Qing; Zhang, Qianning; Miao, Liyun; Zhou, Yujie (Frontiers in Oncology, 2022)
Background: Interstitial lung disease (ILD) is the most serious complication in lung cancer patients with pre-existing ILD receiving chemotherapy. The influence of anti-angiogenic drugs on lung cancer patients with pre-existing ILD remains unclear. We examined the effect of anti-angiogenic drugs on reducing ILD progression risk in non-small cell lung cancer (NSCLC) patients receiving chemotherapy. Methods: We analyzed incidence of ILD progression and outcomes of 52 patients with advanced NSCLC with ILD who received first-line chemotherapy with (anti-angiogenic group, n = 22) and without (non-anti-angiogenic group, n = 30) anti-angiogenic drugs between August 2014 and January 2021. Results: The incidences of chemotherapy-related ILD progression were significantly lower in the anti-angiogenic than in the non-anti-angiogenic groups (0% vs. 20.0%, p = 0.033). However, there were no differences in other events as the competing risk factors of ILD progression between the two groups. The overall-cumulative incidence of ILD progression during the first-line and subsequent chemotherapy was 30.8% (16 of the 52). The median progression-free survival had no significant difference between the anti-angiogenic and the non-anti-angiogenic groups (10.3 vs. 8.1 months, p = 0.386). Conclusions: The addition of anti-angiogenic drugs to chemotherapy regimens may reduce the risk of chemotherapy-related ILD progression in patients with NSCLC-ILD.